The Moderating Effect of Personal Character and Mediating Effect of Organizational Citizenship Behavior on Ethical Orientation of HRM-Ethical Behavior Linkage. - Renusha, M.; Opatha, H.H.D.N.P. (Sri Lankan Journal of Human Resource Management, 2023)
Ethical behavior of employees is an essential individual behavior for survival, success, and growth of any organization. Hardly theoretical arguments and empirical evidence are found with regard to the mediating effect of Organizational Citizenship Behaviour (OCB) on Ethical Orientation of Human Resource Management (EOHRM)-Ethical Behavior (EB) linkage, and the moderating effect of employees’ Personal Character (PC) on EOHRM-EB linkage. An empirical survey study was carried out to achieve four specific research objectives established in respect of the network of relationships and effects occurring among the four constructs. A self-administered and structured questionnaire consisting of four instruments measuring the four constructs was used to collect data from 174 branch managers of Licensed Commercial Banks in Sri Lanka to conduct a cross-sectional study. The five hypotheses formulated by basing on two general theories (General System Theory and EDAP Model), arguments, empirical evidence, and logical beliefs of the researchers under the deductive approach were tested. It was substantiated that EOHRM significantly and positively related to EB of employees and this relationship was mediated significantly by OCB and was moderated significantly by PC. The implications were discussed.
Keywords: Ethical Behavior; Ethical Orientation of Human Resource Management; Organizational Citizenship Behavior; Personal Character